The naughty lamb - Blanchard, Arlene; Wells, Tony (New York : Dial Books for Young Readers, 1989)
Ma Ma Sheep looks all over the farm for Ba Lamb who has decided to go exploring on her own.
Booklist
2.0
K-3
Keywords: Sheep -- Fiction; Domestic animals -- Fiction; Farm life -- Fiction; Hide-and-seek -- Fiction; Sheep -- Fiction; Domestic animals -- Fiction; Farm life -- Fiction